PELUANG EKONOMI TANAMAN CIPLUKAN (Physalis angulata L) SEBAGAI ABATE ALAMI - Wahyu Setya Ratri; M. Th. Darini (Science Tech: Jurnal Ilmu Pengetahuan dan Teknologi, 2016)
Dengue shock system (DSS) is disease that is caused by virus and attacks the thrombosis of human being that may break the blood vessel and may cause death. This disease is caused by mosquito named Aedes aegypty whose cycle is five years and its proliferation is very quickly     (7 days). Preventive efforts that have been done so far is by relying on chemical medicines by fogging and the use of Abate in which it may cause dependency on it and residue of mosquitoes. The content of Abate that kills mosquito larva is themephose, that is a compound organic phosphate which is the same as papain from papaya (Carica papaya L). The  content of this compound kills the growth of mosquito larva by slowing down the rate of metabolism in their bodies. The content of compound in Ciplukan (Physalis angulata L) plants is chosen because it does not contain residue on the environments and, on the contrary, if is unintentionally drunk by people will minimize the effect of suffering from diabetes. This research used Ciplukan (Physalis angulata L) plant extract, particularly from its leaves and stems because its content of alkaloid is more than the content of themephose in Abate; that is 4.06 ppm and 1,56 ppm per 100 gram of the plant (Abate 1 ppm per 100 gram), so in term of activity it is proven that by using the leave extract can kill the mosquito larva in shorter time, less than 24 hours with concentration 100%. Meanwhile, in the stem solution, the percentage of the death of larva is almost the same as the papaya solution, in which it takes less than 78 hours with concentration 100%. It was supported by the result of test using CRD from which it was known that leave extract has larger coefficient than stem extract. It means that the capability of the leave extract (deviation standard 12.43s) is larger than  the stem extract (deviation standard 7.2s). Compared to the use of Abate, the average death of mosquito larva by using leave extract is 26.9 larva per day and compared to the use of stem extract, the average death of mosquito larva is 3.93 larva per day. Economically, we can save Rp 11.350,00/pack if we take Ciplukan leaves and stem to be extracted in which it consists of 10 grams of  Ciplukan leave and stem extract. If the extract or natural Abate is sold, it will cost Rp 650,00/pack; it is more economical than the price of chemical Abate in which price Rp 12.000,00/pack. From the calculation, it is so profitable if we run business on it. We can get back our capital for one year, in which the break event point (BEP) can be reached after selling 162 units which cost Rp 162.000,00 and the profit is more or less Rp 283.000,00/ each production